The Effect of Work Overtime and Organizational Commitment on Employee Performance: The Moderating Role of Leader-Member Exchange (LMX) in Human Resource Management - M Irfan Dwi Syambara; A Zuliansyah; Zathu Restie Utamie (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This study aims to analyze the effect of overtime work and organizational commitment on employee performance, with leader-member exchange (LMX) as a moderating variable in the perspective of Human Resource Management. The MSDI approach views humans as intact work subjects, which must be managed by paying attention to spiritual, ethical, and humanitarian aspects. The research method used is quantitative with a survey approach, and the data is analyzed using Moderated Regression Analysis (MRA). The results showed that overtime work has a positive and significant effect on employee performance. Meanwhile, organizational commitment shows a positive and significant effect on employee performance. The findings also show that LMX significantly moderates the effect of overtime work variables on employee performance, where a good superior-subordinate relationship can strengthen the positive impact. LMX moderates with the weakening path of the organizational commitment relationship and has a negative impact on employee performance. These results indicate the importance of humanistic approaches and Islamic values in the management of human resources to improve performance in a sustainable manner